A Clinical Study to Evaluate the Efficacy of Bala TailaPichu Compared with Jatyadi Taila Pichu in the Management of Parikartika w.s.r. to Acute Fissure-in- Ano - Rao, Varsha M; Yakkundi, R C (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: The squamous mucosa of the lower half of the anal canal is prone to superficial ulceration,which presents as an anal fissure.In Ayurveda, Parikartika is described as one of the commonest ailments of guda pradesha. Parikartika is described as the vyapat/complication of other diseases, like, vamana-virechana vyapat and basti vyapat. The location, signs and symptoms explained in Ayurveda resemble the description of Fissure-in-ano. Fissure-in-ano may occur due to various reasons like constipation, tuberculosis, Crohn’s disease etc. The treatment procedures mentioned for Parikartika in Ayurveda are Anuvasana/matra basti, pichu, parisheka, lepa with Sneha dravyas. Aims and objectives: Evaluation and comparison of the effects of Bala taila pichu and Jatyadi taila pichu in Parikartika w.s.r. to Acute Fissure-in-ano. Materials and Methods: A clinical trial conducted on 60 patients with established cases of Acute fissure-in-ano, divided them into two groups of 30 patients each. The patients were selected fromdepartment of Shalya tantra in Sri Shivayogeeshwar Rural Ayurveda Medical College and Hopsital, Inchal, Belagavi. Group 1 - Bala taila pichu for 7 days. Group 2- Jatyadi taila pichu for 7 days. Results: After completion of this study, there was marked improvement in the signs and symptomsof the condition, with the treatment with both Bala taila pichu and Jatyadi taila pichu. Introduction: The squamous mucosa of the lower half of the anal canal is prone to superficial ulceration,which presents as an anal fissure.In Ayurveda, Parikartika is described as one of the commonest ailments of guda pradesha. Parikartika is described as the vyapat/complication of other diseases, like, vamana-virechana vyapat and basti vyapat. The location, signs and symptoms explained in Ayurveda resemble the description of Fissure-in-ano. Fissure-in-ano may occur due to various reasons like constipation, tuberculosis, Crohn’s disease etc. The treatment procedures mentioned for Parikartika in Ayurveda are Anuvasana/matra basti, pichu, parisheka, lepa with Sneha dravyas. Aims and objectives: Evaluation and comparison of the effects of Bala taila pichu and Jatyadi taila pichu in Parikartika w.s.r. to Acute Fissure-in-ano. Materials and Methods: A clinical trial conducted on 60 patients with established cases of Acute fissure-in-ano, divided them into two groups of 30 patients each. The patients were selected fromdepartment of Shalya tantra in Sri Shivayogeeshwar Rural Ayurveda Medical College and Hopsital, Inchal, Belagavi. Group 1 - Bala taila pichu for 7 days. Group 2- Jatyadi taila pichu for 7 days. Results: After completion of this study, there was marked improvement in the signs and symptomsof the condition, with the treatment with both Bala taila pichu and Jatyadi taila pichu.